Comparative analysis of twelve mitogenomes of Caliscelidae (Hemiptera: Fulgoromorpha) and their phylogenetic implications - Nian Gong (PeerJ Inc., 2021)
Here, the complete mitochondrial genomes (mitogenomes) of 12 Caliscelidae species, Augilina tetraina, Augilina triaina, Symplana brevistrata, Symplana lii, Neosymplana vittatum, Pseudosymplanella nigrifasciata, Symplanella brevicephala, Symplanella unipuncta, Augilodes binghami, Cylindratus longicephalus, Caliscelis shandongensis, and Peltonotellus sp., were determined and comparatively analyzed. The genomes varied from 15,424 to 16,746 bp in size, comprising 37 mitochondrial genes and an A+T-rich region. The typical gene content and arrangement were similar to those of most Fulgoroidea species. The nucleotide compositions of the mitogenomes were biased toward A/T. All protein-coding genes (PCGs) started with a canonical ATN or GTG codon and ended with TAN or an incomplete stop codon, single T. Among 13 PCGs in 16 reported Caliscelidae mitogenomes, cox1 and atp8 showed the lowest and highest nucleotide diversity, respectively. All PCGs evolved under purifying selection, with atp8 considered a comparatively fast-evolving gene. Phylogenetic relationships were reconstructed based on 13 PCGs in 16 Caliscelidae species and five outgroups using maximum likelihood and Bayesian inference analyses. All species of Caliscelidae formed a steadily monophyletic group with high support. Peltonotellini was present at the basal position of the phylogenetic tree. Augilini was the sister group to Caliscelini and Peltonotellini.